Indoor radon measurements and methodologies in Latin American countries - Canoba, A.; Lopez, F. O.; Arnaud, M. I.; Oliveira, A. A.; Neman, R. S.; Hadler, J. C.; Iunes, P. J.; Paulo, SR; Osorio, A. M.; Aparecido, R.; Rodriguez, C.; Moreno, V; et al. (Elsevier B.V., 2001)
According to the current international guidelines concerning environmental problems, it is necessary to evaluate and to know the indoor radon levels, specially since most of the natural radiation dose to man comes from radon gas and its progeny. Several countries have established National Institutions and National Programs for the study of radon and its connection with lung cancer risk and public health. The aim of this work is to present the indoor radon measurements and the detection methods used for different regions of Latin America (LA) in countries such as Argentina, Brazil, Ecuador, Mexico, Peru and Venezuela. This study shows that the passive radon devices based on alpha particle nuclear track methodology (NTM) is one of the more generalized methods in LA for long term indoor radon measurements, CR-39, LR-115 and Makrofol being the more commonly used detector materials. The participating institutions and the radon level measurements in the different countries are presented in this contribution. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: indoor radon; detection methodologies; Latin American countries